المشكلات التي تواجه طلبة الدراسات العليا في تحليل البيانات في البحوث التربوية - Zenib Mohamed Alfegeh (Abjadia, 2018)
خلفية البحث إن عملية تحليل البيانات حظيت بأهمية كبيرة ومتزايدة في جميع البحوث العلمية الإنسانية والإجتماعية والثقافية، على مستوى المعاهد والجامعات، لقدرتها على الوقوف على حقائق المعطيات بكيفية فعّالة وخصوصاً عند الطلبة المقبلين على التخرج. وهدفت هذه الدراسة للوصول إلى فهم أفضل لمفهوم تحليل البيانات. حيث تم في هذه الدراسة تسليط الضوء على أهمية وطريقة تحليل البيانات في البحث، ومفهوم تحليل البيانات، وكذلك دور الدراسات السابقة في عملية التحليل، ومعرفة مراحل تحليل البيانات، ومتطلبات التحليل الكمي والكيفي في البحوث، مع توضيح لتحليل البيانات الكيفية، مع معرفة أهم المشكلات التي تواجه طلبة الدراسات العليا في تحليل البيانات. وقد اتبعت الباحثة في هذه الدراسة المنهج الكيفي لجمع البيانات بإستخدام أدوات جمع البيانات الكيفية. واتضح لنا من خلال النتائج المتوصل إليها بأنه من المشكلات التي يواجهها الباحث النوعي (الكيفي) إثبات مصداقية تحليله وبيان أن نتائج تحليله ليست مجرد انطباعات. وهذا ما يغفل عنه كثير من الباحثين المبتدئين. ومن مشكلات التحليل الإحصائي في البحث الكمي: مشكلات الحصر الشامل وفي هذا النوع من الإحصاء يقوم الباحث بدراسة المجتمع بشكل كامل دون استثناء أي فرد من أفراده، ويستخدم معظم الباحثين الأسلوب الإستدلالي، ويعد هذا أول خطأ يقع فيه الباحثين، وكذلك من مشكلات دراسة العينة عندما الباحث يحدد حجم العينة ومن ثم يبدأ بدراستها باستخدام الأسلوب الاستدلالي، وهنا يواجه سؤالاً هاماً وهو الأساس الذي اعتمد عليه في تحديد نسبة العينة التي سيقوم بدراستها؟ ومع مشكلات الاستبانة والصدق والثبات في حال عدم امتلاك الباحث للخبرة الكافية في التعامل معها. كما أنّ من أكبر المشكلات التي تواجه الباحث هي عدم اختيار المقياس الاحصائي المناسب. Background The analysis of data has been of great and increasing importance in all human, social and cultural scientific research, at the level of institutes and universities, for their ability to identify the facts of the data in an effective manner, especially for students who are graduating. This study aimed to gain a better understanding of the concept of data analysis. In this study, we highlight the importance and method of data analysis in research, the concept of data analysis, the role of previous studies in the analysis process, knowledge of the stages of data analysis, quantitative and qualitative analysis of research, Facing graduate students in data analysis. In this study, the researcher followed the qualitative approach to data collection using qualitative data collection tools. It has become clear to us through the results that it is one of the problems faced by qualitative researcher to prove the credibility of his analysis and to show that the results of his analysis are not mere impressions. This is overlooked by many junior researchers. The problems of statistical analysis in quantitative research: the problems of comprehensive inventory In this type of statistics, the researcher study the community without exception any individual members, and use most of the researchers the method of induction, and this is the first error in which the researchers, as well as the problems of studying the sample when the researcher Determine the size of the sample and then begin to study using the method of induction, and here faces an important question, which is the basis on which to determine the proportion of the sample to be studied? And with problems of resolution, honesty and consistency in the absence of the researcher to have sufficient experience in dealing with them. Also, one of the biggest problems facing the researcher is not to choose the appropriate statistical scale.